Strength and conditioning considerations for speed climbing - Ehiogu, U. D.; Krawczyk, M.; Tallent, J. (Strength and Conditioning Journal, 2023)
Climbing has developed into a professional sport with worldwide participation. Olympic climbing consists of lead climbing, speed climbing, and bouldering. The objective of speed climbing is to reach the top of the route in the fastest time. Speed climbing has not been subjected to the same level of investigation as other types of climbing. A strength and power base underpins performance in speed climbing. This physiological and mechanical basis provides the foundations for effective program design for the speed climber. Effective programming should incorporate a long-term planning approach that is based on a needs analysis of the sport and the climber's physical qualities. The development of high performance will involve the sequential application of regional hypertrophy, maximal strength, explosive strength training, plyometrics, and climbing-specific training to a varying degree.